Exploring the xylem-sap to unravel biological features of Xylella fastidiosa subspecies pauca ST53 in immune, resistant and susceptible crop species through metabolomics and in vitro studies - Surano, Antony; del Grosso, Carmine; Musio, Biagia; Todisco, Stefano; Giampetruzzi, Annalisa; Altamura, Giuseppe; Saponari, Maria; Gallo, Vito; Mastrorilli, Piero; Boscia, Donato; Saldarelli, Pasquale (Frontiers in Plant Science, 2024)
Xylella fastidiosa subsp. pauca ST53 (Xfp) is a pathogenic bacterium causing one of the most severe plant diseases currently threatening the olive-growing areas of the Mediterranean olive growing areas, the Olive Quick Decline Syndrome (OQDS). The majority of the olive cultivars upon infections develop more or less rapidly develop severe desiccation phenomena, while few are resistant (e.g. Leccino and FS17), being less impacted by the infections. The present study contributes to elucidating the basis of the resistance phenomenon by investigating the influence of the composition of the xylem sap of plant species on the rate of bacterial multiplication. Xylem saps from Xfp host and non-host species were used for growing the bacterium in vitro, monitoring bacterial growth, biofilm formation, and the expression of specific genes. Moreover, species-specific metabolites, such as mannitol, quinic acid, tartaric acid, and choline were identified by non-targeted NMR-based metabolomic analysis in olive, grapevine, and citrus. In general, the xylem saps of immune species, including grapevine and citrus, were richer in amino acids, organic acids, and glucose. The results showed greater bacterial growth in the olive cultivar notoriously susceptible to Xfp (Cellina di Nardò), compared to that recorded in the resistant cultivar Leccino. Conversely, higher biofilm formation occurred in Leccino compared to Cellina di Nardò. Using the xylem saps of two Xfpimmune species (citrus and grapevine), a divergent bacterial behavior was recorded: low planktonic growth and biofilm production were detected in citrus compared to the grapevine. A parallel evaluation of the expression of 15 genes showed that Xfp directs its molecular functions mainly to virulence. Overall, the results gained through this multidisciplinary study contribute to extending the knowledge on the host-pathogen interaction, while confirming that the host response and resistance mechanism have a multifactorial basis, most likely with a cumulative effect on the phenotype.